The fifth stroke: the effect of learning the dolphin-kick technique on swimming speed in 22 novice swimmers - Collard, L.; Gourmelin, E.; Schwob, V. (Journal of Swimming Research, 2013)
Can novice swimmers learn to swim faster other than by practicing the 4 official surface strokes (butterfly, backstroke, breaststroke and front crawl)? The present study of 2 matched groups of 10 and 12 young swimmers (aged 9-10) of both genders was designed to answer this question. One group was taught the 4 official strokes in 23 standard swimming lessons. By copying the fastest-?moving sea mammal, the other group performed underwater undulations (dolphin kicks) for between a third and a half of each of their 23 swimming lessons. The dolphin-kick group made greater progress in a 25-metre freestyle time trial with an in-water start (T= 3.48 in Student's T test; p<0.01) -emphasizing the potential of this technique in terms of pure speed. Novice swimmers could be benefit from learning this "fifth stroke".